2019
DOI: 10.1002/cctc.201900090
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen‐Deficient Ti0.9Nb0.1O2‐x as an Efficient Anodic Catalyst Support for PEM Water Electrolyzer

Abstract: Herein, the low cost and efficient oxygen‐deficient Ti0.9Nb0.1O2‐x as support of IrO2 (noted as IrO2/TNO) anode catalyst for the PEM water electrolyzer is synthesized and then characterized using a series of techniques. Oxygen vacancies are introduced by hydrogenation treatment. The IrO2/TNO sample after hydrogenation (noted as IrO2/TNO−Hx, x corresponds to the hydrogenation temperature) exhibits enhanced electronic conductivity and increased surface active sites relative to that of the pristine IrO2/TNO sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 53 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…In addition, EIS curves of the IrO x /F‐TiO 2 ‐based cell before and after the stability test were shown in Figure 4d. R Ω is the overall ohmic resistance of the cell, [24] the values before and after the stability test are 0.081 and 0.098 Ω, respectively. As a small fraction of overall components in the cell, the change of R Ω value for the F‐TiO 2 support is bound to be much smaller than 17 mΩ, again indicating its stable feature.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, EIS curves of the IrO x /F‐TiO 2 ‐based cell before and after the stability test were shown in Figure 4d. R Ω is the overall ohmic resistance of the cell, [24] the values before and after the stability test are 0.081 and 0.098 Ω, respectively. As a small fraction of overall components in the cell, the change of R Ω value for the F‐TiO 2 support is bound to be much smaller than 17 mΩ, again indicating its stable feature.…”
Section: Resultsmentioning
confidence: 99%
“…The electrical conductivity of the support is an important metric toward low Ir-loading catalyst layers. Doping TiO 2 with a foreign element such as Nb, [107,108] V, [109] and W [110] can increase its electrical conductivity. Zhao et al [110] reported a promising performance of 38 wt% Ir nanoparticles loaded on W x Ti 1−x O 2 catalyst.…”
Section: Catalyst Coated Membranementioning
confidence: 99%
“…Therefore, the same approach as for tin‐oxide was applied and various dopings of the titanium dioxide were studied. [ 162 , 163 , 164 , 173 , 174 , 175 , 176 ] Doped TiO 2 support has already been studied for PEMFC application and porous and conductive materials could be obtained. [ 177 , 178 , 179 , 180 , 181 ] Following the promising results from Chen et al.…”
Section: Proposed Supports For Ir Nanoparticlesmentioning
confidence: 99%